Microalgae biorefineries: applications and emerging technologies (2018)
Microalgae transform CO2 into a broad portfolio of biomolecules, and thus should be considered as a valuable biotechnological platform. Despite several research programs and global efforts to establish a sustainable microalgae-based industry, most applications have not transcended academic boundaries. This limitation raises from the high transformation costs when target products are biofuels or fertilizers. Microalgae biorefinery emerges as an alternative to improve economic competitiveness, as Under such a model scope, the process inputs come from industrial waste, while biomass exploitation prioritizes the highest value molecules followed by extraction of less valuable compounds. This review describes a wide range of microalgae exploitation schemes focused on new uses of its constituents, while discussing emerging technologies designed to improve production and efficiencies as well.